Geochemical Characterization and Origin of High-Sulfur, Heavy Oils in Jiyang Sub-Basin, East China - Wang, Guangli; Wang, T.; Zhang, L. (Geological Society of China, 2011)
High-sulfur, heavy petroleum is widely occurring in the Tertiary lacustrine Jiyang sub-basin, Bohai Bay Basin. They are differentiated into two families based on the bulk properties and biomarker compositions. Family 1 is characterized by high resins (40%–71%) and sulfur (2%–4%), and low wax (1%–6%), with n-alkanes removed by biodegradation, whereas family 2 is characterized by extremely abundant sulfur (3%–10%), and high asphaltenes (7%–31%) and wax (2%–19%), with no evidence of microbial attack. The oils of family 1 are distributed in the reservoir, lower than 1500 m throughout the sub-basin. Biomarker assemblages, such as low pristane/phytane ratios (<1 Pr/Ph) and a high abundance of carotane, gammacerane, and dinosterane, suggest that they are derived from the calcareous mudstones and shales among the stratified, saline Esu4 unit, in addition to the in situ biodegradation-concentrated sulfur content. However, the oils of family 2 are identified only in the western Zhanhua and eastern Chezhen depressions, with a depth deeper than 1700 m. Physical properties, together with biomarker ratios, including even-numbered n-alkanes, <1 Pr/Ph, trace diasteranes, higher C35 homohopanes, and abundant dibenzothiophene series, with >1 dibenzothiophene/phenanthrene, indicate an origin from carbonate source rocks. The X-ray diffraction analysis showed that the carbonate source rock is limited in the Esu4 unit of the Bonan sag, which is different from most other source rocks in the same horizon. It is suggested that the high-sulfur, heavy oils are generated at the early stage of the oil window. Bacterial sulfate reduction might be responsible for the occurrence of sulfur species in the high-sulfur, heavy oils, while heavy biodegradation will enhance sulfur concentrations.